COMPOSITIONAL VARIATIONS IN OULANKAITE AND A NEW SERIES OF ARGENTOAN OULANKAITE FROM THE LUKKULAISVAARA LAYERED INTRUSION, NORTHERN RUSSIAN KARELIA - Barkov A.Y.; Fleet M.E.; Martin R.F.; Tarkian M. (My University, 2004)
Oulankaite. a complex base- and precious-metal stannosulfotelluride from the Nadezhda deposit in the Lukkulaisvaara layered intrusion. northern Karelia, northwestern Russia, exhibits a considerable variation in composition. At the type locality, this unique species of platinum-group mineral (PGM) is associated with various base-metal sulfides and PGM in hydrothermally altered pods and stringers of coarse-grained to pegmatitic gabbronorite, located within a sill-like body of microgabbronorite. Covariations in contents of (Pd + Pt) and (Cu + Fe + Ag) are observed in Ag-poor oulankaite (<0.1 wt.% Ag) and in a new compositional series of argentoan oulankaite (up to 1.52 Ag atoms per formula unit, apfu: Sigmaatoms = 14). On the basis of the new data. we suggest a revised generalized formula for oulankaite: (Pd,Pt)(5+x)(Cu,Fe,Ag)(4-x)SnTe2S2, with 0 less than or equal to x < 1. The formula of the Ag-dominant analogue of oulankaite is similar: (Pd,Pt)(5+x)(Ag,Cu,Fe)(4-x)SnTe2S2, with 0 less than or equal to x < 1. Two different mechanisms of substitution exist in argentoan oulankaite, Ag-for-Cu and Pd-for-(Cu+Ag), whereas the composition of Ag-poor oulankaite is dominated by Pd-for-Cu substitution. Argentoan oulankaite ranges up to (Pd5.31Pt0.17)(Sigma5.48)(Ag1.52Cu1.27Fe0.63)Sigma(3.42)Sn(1.03)Te(2.09)S(1.98), which is likely an unnamed species of PGM. Micro-inclusions of Cl-rich ferropargasite (up to 3.25 wt.% Cl) occur in argentoan oulankaite and Ag-poor oulankaite. The argentoan oulankaite solid-solution probably formed from microvolumes of a late-stage liquid or fluid rich in Pd, Ag, Cu, Sn, Te, and S, which is consistent with the Pd-(Pt)-Ag mineralization in the Nadezhda deposit.
Keywords: oulankaite; solid solution; sulfotelluride; platinum-group elements; platinum-group minerals; layered intrusion; Lukkulaisvaara; Russian Karelia; Baltic Shield